Domain structure of the antiferromagnetic insulating state in Nd0.5Sr0.5MnO3 - Shklyarevskiy, I. O.; Shvedun, M. Yu.; Gnatchenko, S. L.; Bentum, P. J. M. van; Cristianen, P. C. M.; Maan, J. C.; Kamenev, K. V.; Balakrishnan, G.; Paul, D. McK (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
Optical reflectivity studies of the ferromagnetic metal (FMM) to antiferromagnetic insulator (AFI) phase transition are performed on Nd0.5Sr0.5MnO3 manganite in a wide temperature and magnetic field range. The formation of a domain structure in the AFI state during the FMM-AFI phase transition is observed. It is shown that the two types of domains observed are energetically equivalent states. On the basis of the experimental results and symmetry analysis we conclude that these domains are crystal twins. The twin domain structure of the AFI state in the Nd0.5Sr0.5MnO3 is visible in reflected unpolarized light due to a different tilting of the surface in the domains. The two-phase domain structure FMM+AFI formed in the vicinity of the phase transition is also studied. It is found that a thermodynamically equilibrium two-phase stripe domain structure does not develop. The absence of the magnetic intermediate state is due to the large energy of the interphase wall, which results in the stripe structure period being much larger than the size of the sample.